2018
DOI: 10.1093/jjco/hyy128
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of lymph node dissection, and oncological outcomes of laparoscopic and open radical nephroureterectomy for patients with urothelial carcinoma of the upper urinary tract undergoing regional lymph node dissection

Abstract: We revealed the feasibility of lymph node dissection (LND) with a laparoscopic approach and the equivalent oncological outcome of laparoscopic nephroureterectomy compared with open nephroureterectomy when regional LND is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Logically, there was no significant effect of the surgical approach on recurrence ( p = 0.1) or mortality ( p = 0.1). Similar results are reported by Abe et al [43] on retrospective data from three Japanese academic centers gathering 214 patients cTanyN0M0. They reported a comparable median LN number between the open group and the pure laparoscopic group (12 vs. 11.5).…”
Section: Results—evidence Synthesissupporting
confidence: 90%
See 1 more Smart Citation
“…Logically, there was no significant effect of the surgical approach on recurrence ( p = 0.1) or mortality ( p = 0.1). Similar results are reported by Abe et al [43] on retrospective data from three Japanese academic centers gathering 214 patients cTanyN0M0. They reported a comparable median LN number between the open group and the pure laparoscopic group (12 vs. 11.5).…”
Section: Results—evidence Synthesissupporting
confidence: 90%
“…Concerning the oncological results, the surgical approach does not seem to make any difference in specialized centers. In the Japanese multicenter study from Abe et al [43], comparable oncological results between open and laparoscopic groups including similar five-year RFS (71.7 vs. 74% ( p = 0.7829)), similar CSS (77.8% vs. 80% ( p = 0.8441)), and similar OS (72.8% vs. 75.9% ( p = 0.3456)). There was no difference between the two approaches for pT3–4 tumors.…”
Section: Results—evidence Synthesismentioning
confidence: 90%
“…Notably, lymph node dissection was not routinely performed in our center because the curative role of lymph node dissection for UTUC remains controversial. 31 , 32 Although some previous articles have described better oncological outcomes when lymph node dissection is performed, 33 , 34 more clinical data and research are still needed to prove the role of lymph node dissection in patients with UTUC.…”
Section: Discussionmentioning
confidence: 99%
“…One Korean study of 371 patients with locally advanced UTUC who underwent RNU reported that LNU had a significantly unfavorable 5-year CSS (LNU 66.1% vs. ONU 80.2%) and was an unfavorable predictor of overall survival (hazard ratio, 2.5) in pT3-4 stage UTUC (p<0.05), whereas another study have shown other contradictory outcomes [ 6 , 18 ]. However, a Japanese study by Abe et al [ 19 ]. of 83 patients with pT3-4 stage did not find any significant difference between LNU and ONU, which was similar to the findings of a large-numbered study.…”
Section: Discussionmentioning
confidence: 99%
“…These results could be explained by the exclusion of early LNU cases, to account for urologists who had not yet overcome the learning curve of the laparoscopic procedure for UTUC. Owing to improved laparoscopic surgical technology, including retroperitoneal lymph node dissection, urologists are able to master the laparoscopic technique more quickly, easily perform nodal dissection, and patients have reduced surgical morbidity with early recovery and a shorter hospital stay without adverse effects on the prognostic outcomes [ 10 , 12 , 19 22 ].…”
Section: Discussionmentioning
confidence: 99%